Embracing Digital Transformation as-a-Service - Zhang, Jonathan Z.; Hon, Hsiao-Wuen (California Management Review, 2020)
Digital transformation (henceforth abbreviated as “DT”) is on the minds of many organizations and promises to modernize firms by optimizing existing processes, enhancing customer experiences, and fostering innovation. Based on the 2018 study by the World Economic Forum and Accenture, DT will realize 100 trillion in value over the next decade. Not only does DT affect businesses’ competitiveness and the consumer experience, but pervasive digitization can profoundly impact many facets of human society - from government services, healthcare, defense, communication, to the future of work and the very definitions of firms and industries. It has the potential to break down socio-economic and cultural barriers. Although many organizations are investing in DT, few are achieving the envisioned results. In a 2018 McKinsey Global survey of over 1700 executives, 80% of the respondents reported that their organizations had begun DT initiatives in recent years, but only 14% mentioned that their efforts have made and sustained performance environment, and an alarmingly low rate of 3% reported complete success at sustaining the change. Against this backdrop of DT’s vast promises and its current unsatisfactory performance, we are also witnessing a recent trend - the morphing of DT from the previous models of discrete consulting engagements and IT integrations to a service model combining multiple technology and service providers on industry vertical platforms offering continuous, seamless, end-to-end transformation with the ability to adapt to changing business environments. We call this emerging model “Digital Transformation as-a-Service.” This model will democratize and accelerate digitization and digital transformation to all facets of society. DTaaS not only provides flexible scalability, it also requires providers to more deeply interface with each other and integrate into the operations of the business to provide continuous adjustments, thereby increasing the success rate for sustained change. Based on our experiences advising organizations on DT initiatives and discussions with diverse stakeholders, we offer guidance for managing and benefiting from DT in the emerging as-a-Service environment to firms and to technology and service providers. In short: Firms should look beyond technology – they need to possess a customer-centric, data-centric, experimental, and adaptive mindset. Technology and service providers need to have a closer alignment among upstream and downstream services and establish industry-vertical platforms to facilitate data sharing and seamless integration across different business functions.